The Influence of Self-Control and Financial Attitude on the Financial Management Behavior of Shopee Paylater Users - Oetama, Seanewati; Susanto, Hari; Alejandra Kristiono, Kezia (International Journal of Science, Technology & Management, 2025)
This study is entitled "The Effect of Self-Control and Financial Attitude on the Financial Management Behavior of Shopee PayLater Users". This study aims to analyze the influence of Self-Control and Financial Attitude on the Financial Management Behavior of Shopee PayLater Users. Financial management behavior is a serious matter among young people, because they grow up amidst a lack of attention to their financial condition and debt that is very easy to obtain through the use of existing financial facilities. Self-Control and Financial Attitude are two factors that are thought to be able to influence Financial Management Behavior. This study uses a quantitative method with primary and secondary data obtained from research objects and data sources obtained through intermediary media. The sample in this study took 60 students of the Sampit College of Economics (STIE) who use Shopee PayLater. The data analysis technique used is multiple linear regression analysis to test the research hypothesis. The results of the study show that the results of the t-test (partial) indicate that Self-Control influences the Financial Management Behavior of Shopee PayLater users. This is evidenced by the value of >, namely 4.995 > 2.000324 with a significance level of 0.001 < 0.05. Financial Attitude influences the Financial Management Behavior of Shopee PayLater users. This is evidenced by the value of 3.425 > 2.000324 with a significance level of 0.001 < 0.05. The F test (simultaneous) shows that Self Control and Financial Attitude influence the Financial Management Behavior of Shopee PayLater users. This is evidenced by the value of 63.299 > 3.16 with a significance level of 0.000 < 0.05. These findings provide implications for Shopee PayLater users in understanding the factors that can influence financial management behavior before making decisions to use the services offered..